2014
DOI: 10.17229/jdit.2014-0620-001
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative in vivo Imaging of Adenosine A2A Receptors in the Human Brain Using 11C-SCH442416 PET: A Pilot Study

Abstract: Abstract:11 C-SCH442416 was reported in preclinical studies with rodents and primates to be the first nonxanthine radioligand suitable for the in vivo imaging of adenosine A 2A receptors with positron emission tomography (PET). The aim of the present work was to investigate the suitability of 11 C-SCH442416 for the in vivo quantification of A 2A receptors in human brain. Methods:Five male healthy subjects were scanned with 364 MBq bolus injections of 11 C-SCH442416. 90 minutes of dynamic PET emission data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The quantifiability of A 2A receptor availability in the striatum and thalamus has been demonstrated in the 11 C SCH 442416 PET study [21]. A single oral dose of 50-200 mg preladenant achieved full A 2A receptor blockade in the striatum.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The quantifiability of A 2A receptor availability in the striatum and thalamus has been demonstrated in the 11 C SCH 442416 PET study [21]. A single oral dose of 50-200 mg preladenant achieved full A 2A receptor blockade in the striatum.…”
Section: Discussionmentioning
confidence: 90%
“…Quantitative in vivo imaging of A 2A receptors in the human brain using 11 C-SCH442416 PET has been recently described [21]. The current study was designed to investigate the A 2A dose-receptor occupancy profile of preladenant in the human brain and to determine plasma concentrations and dose of preladenant that result in inhibition of 11 C-SCH 442416 binding at 1, 6 or 12 hours after single oral administration of 10, 50 and 200 mg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, they are over-expressed in activated microglia and are considered an alternative to TSPO as a target for imaging neuroinflammation (Tronel et al, 2017). (Grachev et al, 2014;Tronel et al, 2017). Studies with the former two tracers showed elevated availability of A 2A R in the striatum of PD patients with dyskinesia, but not in dyskinesia-free PD patients (Mishina et al, 2011;Ramlackhansingh et al, 2011).…”
Section: Other Targetsmentioning
confidence: 99%
“…In the healthy CNS, human in vivo PET studies demonstrate greatest A 2A receptor ligand binding in the basal ganglia, whereas low radiotracer accumulation was shown in cortical areas and cerebellum [ 19 , 129 131 ]. Subject age does not seem to affect striatal A 2A receptor radioligand binding [ 132 ].…”
Section: A 2a Receptor-binding Radioligands In mentioning
confidence: 99%